Antenna Array Simulation and Detection Performance Analysis of Sanya Prototype Incoherent Scatter Radar. Issue 6 (20th June 2018) - Zhao, Hailong; Yao, Ming; Deng, Xiaohua; Yuan, Kai; Ding, Feng; Zeng, Lingqi; Li, Chen
Abstract: Incoherent scatter radars have become an important means of ionospheric detection, which is the only ground instrument that can detect important plasma parameters over the entire ionosphere (60–2, 000 km). In Sanya of China, the advanced high‐power phased array incoherent scatter radar is under construction. The radar has the advantages of continuous observation, full space coverage, and rapid scanning. Usually, since the plasma‐scattered signal is weak, the estimation of signal‐to‐noise ratio (SNR) and relative error is significant for radar detection performance analysis. Major factors affecting the detection performance, such as power aperture product, pulse width, daytime and nighttime, and different antenna gains (zenith angles), are investigated in the present study. Details of the impacts of these factors on the radar performance are analyzed. According to analysis, the SNR and the detection range could be enhanced significantly by increasing the power aperture product. The integration significantly reduces the relative error; for instance, the relative error could reach 5% in the range of 80–700 km by a few seconds' integration. The SNR decreases with the range resolution improving. The detection performance during nighttime is worse than that of daytime. Furthermore, the SNR decreases with the increasing zenith angle. However, the detection performance can be compensated by the integration. Once the radar becomes operational practically, the numerical simulation results will help to choose the appropriate operation parameters to achieve the best operational performance with given budget of operation cost. Key Points: The beam pattern of the phased array antenna was studied numerically The detection performance is estimated by evaluating the SNR and the relative errors The detection performance of different antenna gains is analyzed